Antiviral lectin Q-Griffithsin suppresses fungal infection in murine models of vaginal candidiasis - Nabeta, Henry W.; Lasnik, Amanda B.; Fuqua, Joshua L.; Wang, Lin; Rohan, Lisa C.; Palmer, Kenneth E. (Frontiers in Cellular and Infection Microbiology, 2022)
Resistance to antifungal agents in vulvovaginal candidiasis has resulted in increasing morbidity among women globally. It is therefore crucial that new antimycotic agents are developed to counter this rising challenge. Q-Griffithsin (Q-GRFT) is a red algal lectin, manufactured in Nicotiana benthamiana. Griffithsin has well characterized broad spectrum antiviral activity and has demonstrated potent in vitro activity against multiple strains of Candida, including C. albicans. We have been working to incorporate Q-GRFT into topical microbicide products to prevent HIV-1 and HSV-2 transmission. The goal of this study was to evaluate the efficacy of a prototype Q-GRFT dosage form in prophylactic and therapeutic murine models of vaginal candidiasis, through microbiologic, histopathologic, and immune studies. In a preventive model, in comparison with infected controls, Q-GRFT treatment resulted in a lower fungal burden but did not alter the number of vaginal neutrophils and monocytes. In a therapeutic model, Q-GRFT enhanced fungal clearance when compared with infected untreated controls. Finally, histopathology demonstrated lower vaginal colonization with C. albicans following Q-GRFT treatment. Our results demonstrate that Q-GRFT has significant preventive and therapeutic activity in vaginal candidiasis offering additional benefit as a topical microbicide for prevention of HIV-1 and HSV-2 transmission.